The efficacy of a gambling prevention program among high-school students - Calado, F.; Alexandre, J.; Rosenfeld, L.; Pereira, R.; Griffiths, M. D. (Journal of Gambling Studies, 2020)
Youth problem gambling has become an emergent public health issue, and adolescents constitute a vulnerable age group for the development of gambling-related problems. Although there is research concerning the risk factors of youth problem gambling, rigorous evaluations of the effectiveness of preventive initiatives is still rare. The present study evaluated the efficacy of an integrative intervention to prevent youth problem gambling based on a multidimensional set of factors including gambling-related knowledge, misconceptions, attitudes, gambling frequency, amount of money spent, total hours spent gambling per week, and sensation seeking. A pre- and post-test design was performed with 111 Portuguese high-school students randomly assigned to two groups (experimental and control). The findings demonstrated that the intervention was effective in improving correct knowledge about gambling, reducing misconceptions and attitudes, and in decreasing the total hours spent gambling per week. The intervention was also effective in reducing the number of at-risk/problem gamblers during the study period. Furthermore, these findings were stable after a 6-week follow-up. Overall, the intervention program appeared to be effective in correcting some gambling-related behaviours, and provides suggestions for future interventions.